Tetrahydropyrazolo[1,5-a]pyridine-fused steroids and their in vitro biological evaluation in prostate cancer - Jorda, Radek; Lopes, Susana M M; Řezníčková, Eva; Ajani, Haresh; Pereira, António V; Gomes, Clara S B; M V D Pinho E Melo, Teresa (European journal of medicinal chemistry, 2019)
The androgen receptor (AR) is a steroid hormone receptor and its high expression and disruption of its regulation are strongly implicated in prostate cancer (PCa) development. One of the current therapies includes application of steroidal antiandrogens leading to blockade of the AR action by the abrogation of AR-mediated signaling. We introduced here novel 4,5,6,7-tetrahydropyrazolo[1,5-a]pyridine-fused steroidal compounds, described their synthesis based on [8π+2π] cycloaddition reactions of diazafulvenium methides with different steroidal scaffolds and showed their biological evaluation in different prostate cancer cell lines in vitro. Our results showed the ability of novel compounds to suppress the expression of known androgen receptor targets, Nkx3.1 and PSA in two prostate cell lines, 22Rv1 and VCaP. Candidate compound diminished the transcription of AR-regulated genes in the reporter cell line in a concentration-dependent manner. Antiproliferative activity of the most promising steroid was studied by clonogenic assay and induction of apoptosis in treated cells was documented by immunoblot detection of cleaved PARP.
Keywords: Male; pyrazolo[1,5-a]pyridine; Molecular Docking Simulation; homeodoménové proteiny; Homeodomain Proteins; Prostatic Neoplasms; protinádorové látky; Pyridines; Humans; Androgen; Antineoplastic Agents; Transcription Factors; mužské pohlaví; Receptors, Androgen; androgenní receptory; pyrazoly; vazebná místa; pyridiny; Cell Line, Tumor; nádorové buněčné linie; simulace molekulového dockingu; nádory prostaty; transkripční faktory; Binding Sites; Pyrazoles; lidé; steroidy; Prostate; Steroid; Steroids; Galeterone